The Imperative of Request of Indonesian and Japanese Language: A Comparative Studies on Politeness - Rachman, Zulfikar (Bina Nusantara University, 2022)
The research aimed to find the imperative of requests and their politeness in the Indonesian and Japanese languages. It also aimed to analyze the similarities and dissimilarities between both languages. The method applied in the research was comparative studies. The data on both languages were collected from novels, movie dialogue, email, questionnaires, SNS (LINE, WhatsApp, Instagram, Facebook), and daily conversation corpus. As a result, the request markers